UTERINE TRANSPLANTATION: OPPORTUNITIES, CHALLENGES, AND FUTURE PERSPECTIVES - Yuldasheva Barnokhonim; Dr. Aziza Farxodovna Rakhmatullayeva (Western European Studies, 2025)
Uterine transplantation has ushered in a new era in reproductive medicine. This procedure is emerging as an effective treatment for infertility related to uterine absence or dysfunction. The article analyzes the clinical opportunities, existing challenges, and future perspectives of uterine transplantation. Special attention is given to patient selection, immunosuppressive therapy, ethical issues, and technological innovations
Keywords: uterine transplantation; infertility; reproductive medicine